Candlelight Protests in South Korea:The Legacies of Authoritarianism and Democratization - Paul Y. Chang (Ewha Journal of Social Sciences, 2018)
The recent candlelight protests in the fall and winter of 2016 and 2017 marked a critical moment in the maturation of South Korean democracy. Through complex connections between contributing actors involving the protesting public, the National Assembly, and the Constitutional Court of the Republic of Korea, President Park Geun-hye became the first South Korea president to be impeached through democratic procedures. While acknowledging the significant differences that distinguish this most recent protest wave with contentious politics of the past, this article highlights the foundational legacies of South Korea’s authoritarian history. In addition, I reflect on how the contemporary candlelight protest industry draws on organizational and cultural resources first established in past democracy movements. In short, the political contest that brought down Park Geun-hye in 2016-2017 was in some tangible and intangible ways a reenactment of the authoritarian and democratization legacies that dominated much of South Korea’s modern history. KCI Citation Count: 5